The Creation of Standard-Setting Videos to Support Faculty Observations of Learner Performance and Entrustment Decisions. (February 2016) - Calaman, Sharon; Hepps, Jennifer H.; Bismilla, Zia; Carraccio, Carol; Englander, Robert; Feraco, Angela; Landrigan, Christopher P.; Lopreiato, Joseph O.; Sectish, Theodore C.; Starmer, Amy J.; Yu, Clifton E.; Spector, Nancy D.; et al.
Abstract : Entrustable professional activities (EPAs) provide a framework to standardize medical education outcomes and advance competency-based assessment. Direct observation of performance plays a central role in entrustment decisions; however, data obtained from these observations are often insufficient to draw valid high-stakes conclusions. One approach to enhancing the reliability and validity of these assessments is to create videos that establish performance standards to train faculty observers. Little is known about how to create videos that can serve as standards for assessment of EPAs. The authors report their experience developing videos that represent five levels of performance for an EPA for patient handoffs. The authors describe a process that begins with mapping the EPA to the critical competencies needed to make an entrustment decision. Each competency is then defined by five milestones (behavioral descriptors of performance at five advancing levels). Integration of the milestones at each level across competencies enabled the creation of clinical vignettes that were converted into video scripts and ultimately videos. Each video represented a performance standard from novice to expert. The process included multiple assessments by experts to guide iterative improvements, provide evidence of content validity, and ensure that the authors successfully translated behavioral descriptions and vignettes into videos that represented the intended performance level for a learner. The steps outlined are generalizable to other EPAs, serving as a guide for others to develop videos to train faculty. This process provides the level of content validity evidence necessary to support using videos as standards for high-stakes entrustment decisions.